PT. ANGKASA PURA II (PERSERO) STRATEGY ININCREASING THE NUMBER OF FOREIGN TOURIST ARRIVAL (FTA) - Rachim, Bianca; Ferezagia, Debrina Vita (UI Scholars Hub, 2019)
The focus of this Journal is to know PT. Angkasa Pura II (Persero) strategy in increasing the number of Foreign Tourist Arrival (FTA) with Low Cost Carrier Terminal (LCCT) Soekarno- Hatta International Airport Development. The type of research in this study is descriptive research. Techniques of data collection are from interviews, observation, and literature. The result of this research says that in building Soekarno-Hatta International Airport Low Cost Carrier Terminal (LCCT) there is some marketing strategy in offering new routes to airlines, such as roadshow, inviting airlines, and bring in airlines. The process of opening new routes takes a long time, depending on the duration of internal airline coordination. For marketing LCCT to the public, PT. Angkasa Pura II (Persero) together with the Ministry of Tourism is making a promotion video that will disseminate in and outside the country.